1996
DOI: 10.1590/s0102-76381996000400007
|View full text |Cite
|
Sign up to set email alerts
|

Resultado clínico tardio da anuloplastia mitral sem suporte em crianças e adolescentes

Abstract: Nesralla I A -Resultado clínico tardio da anuloplastia mitral sem suporte em crianças e adolescentes. Rev Bras Cir Cardiovasc 1996; 11 (4): 263-9.RESUMO : O resultado clínico pós-operatório (p .o.) tardio da reconstrução da valva mitral sem suporte em crianças e adolescentes é analisado através da observação de uma série de 70 pacientes operados. Objetivou-se acompanhar a evolução clínica tardia após o tratamento de insuficiência mitral pelas técnicas reparadoras nos pacientes em fase de crescimento, avaliar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Hospital and late mortality was considered very low when compared to other authors. BORDIGNON et al [29] reported hospital and late mortality rates of 4.3% and 8.6% respectively in a series of 20 children.…”
Section: Commentsmentioning
confidence: 94%
“…Hospital and late mortality was considered very low when compared to other authors. BORDIGNON et al [29] reported hospital and late mortality rates of 4.3% and 8.6% respectively in a series of 20 children.…”
Section: Commentsmentioning
confidence: 94%
“…Rheumatic disease is one of several causes of mitral insufficiency and it is, without doubt, the most frequent [17].…”
Section: Commentsmentioning
confidence: 99%
“…Mitral valvuloplasty currently is the preferred procedure for the correction of mitral insufficiency [17], and its use should be encouraged [18] mainly with children.…”
Section: Commentsmentioning
confidence: 99%
“…This technique has a late result comparable to more complex support technqiues [30][31][32][33][34] , but with a lower incidence of technical repair failure. The reported incidence of repair failure due to technical problems with the prosthetic ring in the adult is varied (Aharon 10 -2.9%; Cosgrove 34 -3.2%; Deloche 35 -4.3%; Cosgrove 24 -3.3%).…”
Section: Survival Yearsmentioning
confidence: 99%